DA'WAH STRATEGY IN THE LIVE SHOPPING ERA: VALUE NEGOTIATION, TRANSACTIONAL ETHICS, AND PERSUASIVE COMMUNICATION - Iin Inayah (Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
Live shopping (livestream commerce) has rapidly evolved from an entertainment-oriented feature into a significant sales channel that blends real-time interaction, creator trust, and impulse-friendly promotional mechanics. This shift creates a distinctive tension for Islamic da'wah: the platform logic of urgency, scarcity, and algorithmic attention can collide with the normative commitments of truthfulness (sidq), trustworthiness (amanah), and fairness in muamalah. This article aims to develop an integrative model of 'Da'wah-First Commerce' for da'wah actors who operate within live shopping ecosystems, emphasizing value negotiation, muamalah ethics, and persuasive communication that remains ethically bounded. Methodologically, the study employs an integrative literature review of research on livestream commerce, consumer trust, parasocial interaction, and Islamic business ethics, complemented by a conceptual synthesis using the mediatisation of religion as an interpretive lens. The synthesis yields three findings: (1) live shopping's persuasive affordances are driven by social presence and parasocial bonds that shape trust and purchase intentions; (2) ethical risks cluster around information asymmetry, guilt/fear-based selling, and performative religiosity; and (3) a layered strategy—core values, operational muamalah safeguards, and 'polite persuasion'—can reduce ethical drift while preserving engagement. The article contributes a practical run-of-show, moderation SOP, and measurable indicators for both da'wah outcomes and commercial outcomes. Implications are discussed for da'wah practitioners, platforms, and regulators seeking a healthier digital marketplace.